Exact values of widths for certain functional classes - Vakarchuk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
For classes of functions analytic in a unit circle in a Hardy-Banach space, we obtain exact values of Kolmogorov widths in the case where the metrics of the class and the space do not coincide.